Relationship Of Cognitive Speed On Scoring Accuracy From Stability In Football Young Players - Hussain Suhail Mathkor Khallati (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The study aimed to identify contribution of perceptual speed to accuracy Goal scoring in football is consistent among a sample of young players. The researcher used descriptive method, and the research sample consisted of 25 young players from a group of 30, all players from Al-Minaa Club in Basra Governorate were selected purposively. Perceptual speed is below required level during scoring, it negatively affects players, which is reflected in player’s performance level, perception may be related to accuracy of scoring from a stationary position in football and contribute significantly to improving level of offensive skills performance among young players. Results show differences in standard deviations of two variables perceptual speed is necessary for young players to perform skill of shooting accuracy in football, player needs tactics and to see what opponent is doing during shooting, and this depends on player’s speed of perceiving stimuli surrounding. Because no matter how complete and effective shooting is at a high level of skill performance, still needs perceptual speed, as calculated value of (T) is 3.82. When comparing it to tabulated value, which is 2.06, we notice that calculated value of (T) is greater than tabulated value, and this indicates its significance. Conclusions was that perceptual speed contributed well to the accuracy of stationary shooting in football among young players, also concluded that it is important to consider perceptual speed in improving stationary shooting accuracy in football for young players, and indeed in various sports as well. Recommendation is to adopt current research cognitive speed in various research and studies due to its very high validity and reliability.